Adapting a quality improvement collaborative to a new national context: a co-design and feasibility study to improve dementia care in Ireland - Michael Sykes; Lauren O’Mahony; Daisy Wiggin; Suzanne Timmons (BMC Health Services Research, 2023)
Abstract Background Adaptation seeks to increase intervention fit with context, an important influence upon implementation. People with dementia in acute hospitals in Ireland do not routinely receive best care. To improve care in Ireland, we sought to adapt an existing quality improvement collaborative, to support the improvement capabilities of recipients of feedback from the Irish National Audit of Dementia. Methods The study followed a staged process to co-design adaptations to reflect contextual differences between the English and the Irish healthcare systems, and to explore feasibility of the adapted Quality Improvement Collaborative in Ireland. We used co-design group meetings involving dementia clinicians from three hospitals, delivered the intervention virtually and interviewed healthcare workers from seven hospitals to adapt and explore the fidelity, affective response and reported appropriateness of the intervention. Results The intervention required adaptation to reflect differences in strategic intention, ways of working and hospital social structures. There was evidence that the adapted intervention generated a positive affective response, was perceived as appropriate and led to fidelity of receipt and response. Conclusion We describe implications for the adaptation of interventions to increase participants’ quality improvement capabilities and highlight the importance of socio-adaptive work. We propose further work to explore antecedents of senior positional leader engagement, to describe the delivery of intra-participant behaviour change techniques and to adapt the intervention to other clinical domains.